ANALISIS TINGKAT TOKSISITAS LIMBAH PEWARNAAN JEANS MENGGUNAKAN IKAN NILA (ORECHROMIS NILOTICUS) - Caroline, Jenny; Handriyono, Rachmanu Eko; Ximenes, Sonia S.; Kusuma, Maritha Nilam (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Jeans dyeing is one of the large or small scale industries that produces liquid waste from the coloring process. Liquid waste that enters the water body will cause environmental pollution. It is necessary to study or test about the nature and characteristics of jeans dye wastewater. One of the tests that can be done is the toxicity test that refers to USEPA (2000) and OECD (2004) standards. Tests carried out by entering the concentration of certain wastewater in 5 (five) reactors with tilapia fish (Oreochromis niloticus) biota. Conducted preliminary research that is the 7 day acclimation process and 1 day range finding test. Running process carried out for 96 hours for fish 5 cm. Analysis was carried out every 24th, 48th, 72th and 96th hour for analysis of temperature, pH, DO, and mortality. Heavy metal (Cr) analysis is carried out in fish bodies and wastewater at each concentration. The initial characteristics of jeans stained liquid waste for pH: 7, temperature: 30, 7ÂºC, DO: 8.5 mg / l, TSS: 1040.0 mg / l; BOD: 137 mg / l; COD: 484.8 mg / l and Total chrome: 3.079 mg / l. The level of LC50 toxicity concentration in tilapia fishÂ fish 5 cm size of 12.59% results obtained from the calculation of probit with excel software. The content of chromtotal (Cr) contained in the test biota for 96 hours ranged from 1.03 l / kg to 1.93 l / kg.